The COVID rehabilitation paradox: why we need to protect and develop geriatric rehabilitation services in the face of the pandemic - Grund, Stefan; Gordon, Adam L; Bauer, Jürgen M.; Achterberg, Wilco P; Schols, Jos M G A (Age & ageing, 2021)
Older multi-morbid persons often fall seriously ill due to COVID-19. To be able to participate in a social life again, they often need special rehabilitation measures. Geriatric rehabilitation is a multi-professional service geared to these needs. Paradoxically, however, capacities in geriatric rehabilitation are currently being reduced despite increasing demand. The reasons are manifold and are not only due to the current situation. This article highlights the current situation leading to the COVID rehabilitation paradox and shows ways to learn from it for the future.